Front Cover: Etherification of 5‐Hydroxymethylfurfural to Biofuel Additive Catalyzed by Aquivion® PFSA Modified Mesoporous Silica (Eur. J. Inorg. Chem. 33/2018). Issue 33 (30th August 2018) - Dou, Youwei; Zhang, Mengyuan; Zhou, Shuai; Oldani, Claudio; Fang, Wenhao; Cao, Qiue
Abstract : The Front Cover shows the fabrication of a PFSA‐functionalized silica hybrid solid acid. Leaching‐resistant SO3 H sites anchored to the silica network via hydrogen bonding and/or electrostatic interactions are highly accessible to reactants. Sufficient mesopores promote the diffusion/transportation of substrates and show shape selectivity to the ternary branched structure of the transition‐state intermediate. Thus, the Aquivion®/ m ‐SiO2 catalyst enables an enhanced production of furanyl ether (66%) at a high conversion of HMF (78%) through direct etherification with isobutene at mild conditions. More information can be found in theFull Paper by W. Fang et al. For more on the story behind the cover research, see theCover Profile .